YOUTUBE USAGE PATTERN AMONG COMMUNICATION SCIENCE STUDENTS - Mukhlis Amin; Ismail Naharuddin (Journal of Information Technology and Its Utilization, 2020)
This study aims to determine the motives and patterns of using youtube among Communication science students. This research was conducted using quantitative methods. Data was collected online using a questionnaire created on Google Form. The questionnaire link was distributed using the crowdsourcing method using Whatsapp. The population of this study were students majoring in Communication Science, Faculty of Social and Political Sciences (FISIP), Makassar Islamic University. We have described both the cognitive motive and the affective motive. Second, we have calculated the value of the motive for both and found that the value of cognitive motive is slightly higher than the value of affective motive. This means that the cognitive motives and affective motives of students in using Youtube are quite balanced.